A CONTRIBUTION TO THE HYDROCHEMISTRY AND WATER TYPOLOGY OF THE AMAZON RIVER AND ITS TRIBUTARIES - Rocha da Silva, Maria do Socorro; Ríos-Villamizar, Eduardo Antonio; Brandão da Cunha, Hillândia; Fonseca Miranda, Sebastião Átila; Filgueiras Ferreira, Sávio José; Bulcão Bringel, Sergio R.; Abrantes Gomes, Núbia; Pascoaloto, Domitila; Monteiro Silva, Luana (Caminhos de Geografia, 2019)
The geological diversity of the Amazon Basin, as well as the pluvial regime, influences the characteristics of the waters. To know the water types of the rivers of the Amazon basin, 288 superficial water samples were collected, 94 of them along the Amazon River and 194 in their tributaries, from March 2009 to September 2012. The physical, chemical, and physicochemical properties were analyzed. Rivers with pH between 6.5 and 7.6 and electrical conductivity (40.00 - 80.00 μS cm-1) are water bodies that are influenced by the Andean region (e.g., the Amazon River and some of its right bank tributaries). On the other hand, the rivers with pH in the range of 3.5 to 5.5 and conductivity